2019
DOI: 10.17557/tjfc.655078
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Fatty Acids Composition and Oil Quality Factors of Some Peanut Varieties Having Different Market Types at Different Harvesting Times in Main and Double Crop Growing Seasons in Mediterranean Region

Abstract: The objective of this study was to determine the fatty acids composition and oil quality factors of some peanut varieties having different market types at different harvesting times in main and double crop growing seasons in Mediterranean region. This study was conducted in the experimental area of the Cukurova University Faculty of Agriculture Department of Field Crops as a main and double crop in 2015 and 2016. The experimental design was a split plot with three replications. Five peanut varieties, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 36 publications
(109 reference statements)
7
12
0
2
Order By: Relevance
“…Significant differences for oil content among the cultivars are attributable to the genetic makeup and place of their origin (Hassan et al, 2005). These results are in agreement with the findings of Raheja et al (1987), Chowdhury et al (2015) and Bakal and Arioglu (2019).…”
Section: Oil Contentsupporting
confidence: 94%
See 1 more Smart Citation
“…Significant differences for oil content among the cultivars are attributable to the genetic makeup and place of their origin (Hassan et al, 2005). These results are in agreement with the findings of Raheja et al (1987), Chowdhury et al (2015) and Bakal and Arioglu (2019).…”
Section: Oil Contentsupporting
confidence: 94%
“…High O/L ratio and low IV value generally indicate good stability and long shelf-life (Worthington et al, 1972;Braddock et al, 1995). Golombek et al (1995), Hinds (1995), Andersen and Gorbet (2002) Isleib et al (2008), Shin et al (2010), Singkham et al (2010), Chowdhury et al (2015), Gulluoglu et al (2017) and Bakal and Arioglu (2019) indicated that the fatty acid composition of peanut oils varies significantly by genotype, soil nutrient, seed maturity, production year and planting date, geographic location of production, and environmental factors including temperature and other seasonal effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, plamitic and stearic acid were ranges from 7.64-12.52% and 0.89-5.26%, respectively (Table 3). Our results are in agreement with the results of other researchers who reported that the palmitic acid content of peanut cultivars was varied between 8.6-14.1% and stearic acid between 1.6-3.7% (24,(29)(30)(31)(32). Recently, it was reported that palmitic and stearic acids percentage values of the peanut varieties were varied between 10.04-12.68% and 2.32-3.36%, respectively (25).…”
Section: Saturated Fatty Acids Compositionsupporting
confidence: 93%
“…The oil content values of our studied varieties were ranged from 49.00 to 51.73% whereas among the hybrids and reciprocal hybrids the values ranged from 46.93 -55.40% (Table 3). According to the published reports, the oil content values of peanut varieties in different market types were ranged from 42.0 to 53.8% in the Spanish type and 43.0-48.0% in Valencia type varieties (23)(24)(25). Therefore, out results goes well in accordance with the results of other researchers.…”
Section: Oil Content In the Parents And Hybridssupporting
confidence: 84%
See 1 more Smart Citation